Territorialidades e com-vivência nas dinâmicas espaciais de um bairro : Mosqueiro - Rabelo, Josevânia Nunes (2022)
In this thesis, I adopted three sociological aspects of Mosqueiro (a district delimited by the cities of São Cristóvão and Aracaju): inhabiting, sailing boat race, and the coconut (well-known dance in northeastern Brazil) as interpretation perspectives. I also cataloged the urban changes in that place from 2010 to 2020. Therefore, that territory belongs to São Cristóvão and, at the same time, has a joint administration with Aracaju. My goal was to understand the territoriality composed of Mosqueiro beach and the intermediation of the Vaza-Barris river since there are varied interests of uses declared by the riverside residents and regular visitors. To understand these spatializations, I observed the typologies of sociability resulting from the valorization of these lands. I also observed the insertion in tourist locality guides, and their spots for sports and entertainment practice. This research is qualitative, based on reflections on the interviews, the questionnaires, and the images produced during this journey. It is limited to everyday life and two ancestral rituals (sailing boat race and the coconut) of the community. This triad establishes the basis of a nucleus of coexistence, meaning the sharing of a way of inhabiting and cultural experiences. Therefore, the structure of this work argues that this “co” is established in the neighborhood by territoriality of the demarcations of being there, in the action of dancing bodies and the tracks that produce a “duration”.